2021
DOI: 10.1039/d0an01997f
|View full text |Cite
|
Sign up to set email alerts
|

Label-free analysis of gingival crevicular fluid (GCF) by surface enhanced Raman scattering (SERS)

Abstract: Surface enhanced Raman scattering can offer rapid and label-free detailed molecular fingerprints of gingival crevicular fluid, reflecting the physiological and pathological states of a single dental element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…Filter paper is not only an easy alternative way to collect biological material; it is also a promising sampling support to simplify and strengthen the label-free analysis of biofluids with SERS. Recently, we demonstrated that the use of a very specific commercial paper (Periopaper ® ) coupled with a centrifugal-driven aggregation of Ag-NPs, allowed for a rapid and reproducible analysis of gingival crevicular fluid with SERS without the need for a deproteinization step [ 22 ]. The first objective of the present work was to investigate whether the same strategy could be applied for the analysis of a protein-rich biofluid such as unprocessed human serum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Filter paper is not only an easy alternative way to collect biological material; it is also a promising sampling support to simplify and strengthen the label-free analysis of biofluids with SERS. Recently, we demonstrated that the use of a very specific commercial paper (Periopaper ® ) coupled with a centrifugal-driven aggregation of Ag-NPs, allowed for a rapid and reproducible analysis of gingival crevicular fluid with SERS without the need for a deproteinization step [ 22 ]. The first objective of the present work was to investigate whether the same strategy could be applied for the analysis of a protein-rich biofluid such as unprocessed human serum.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously addressed these issues by sampling a biofluid before the post-immobilization process, resulting in strong and reproducible SERS signals [ 22 ]. Here, we extend our previous work by optimizing a novel protocol for label-free SERS sensing of unprocessed human serum.…”
Section: Introductionmentioning
confidence: 99%
“…Example of how characteristic ET bands (highlighted with grey areas) are observed in LF‐SERS spectra of a variety of human biofluids of healthy donors. SERS spectrum of (a) ET [19] is compared to SERS spectra of (b) erythrocytes lysate [19], (c) serum [29], (d) gingival crevicular fluid [28], (e) seminal plasma [50] and (f) cerebrospinal fluid [32]. All spectra were obtained with an excitation at 785 nm, and using Ag nanoparticles as substrates, with the exception of (f), for which Au nanoparticles were used.…”
Section: Et In Lf‐sers Of Biofluidsmentioning
confidence: 99%
“…Interestingly, some recent studies characterizing biofluids with LF-SERS have linked ET with crucial metabolic processes, such as inflammation and antioxidant capacity, in several disease conditions (e.g. gingivitis [28], hepatocellular carcinoma [29], large B-cell lymphoma [30] and myeloma [31]). On the other hand, many other studies, most of which were published before the SERS spectrum of ET was reported, inadvertently assigned ET bands to other molecules or left them unassigned.…”
Section: Et In Lf-sers Of Biofluidsmentioning
confidence: 99%
See 1 more Smart Citation